The Influence of Parenting Style and Stimulation on Social-Emotional Development: Study of Stunting and Not Stunting Toddlers in Bogor Regency - Aziizah, Nidaa Fauziyyatun Nur; Latifah, Melly (Journal of Family Sciences, 2024)
Stunting is a chronic nutritional problem that can disrupt children's growth and development, one of which is social-emotional development. This research generally aims to analyze the influence of parenting style and social-emotional stimulation on children's social-emotional development. The research design uses explanatory survey methods. The research involved 41 stunting toddlers and 41 non-stunting toddlers aged 2-3 years and their mothers as main caregivers who were selected purposively and lived in Cibodas Village, Rumpin District, Bogor Regency, West Java on July 2023. Data were processed and analyzed using Microsoft Excel 2016 software and IBM Statistical Package for Social Science (SPSS) Statistics 26 software. The results show that stunting toddlers are more commonly found in boys, families with low-educated mothers and fathers, and low incomes. Even so, in this study no significant different test results were found. The results of the correlation test show that age of father and mother is significantly positively related to authoritative parenting style. It can be interpreted that as father and mother get older, the authoritative parenting style is possibly applied more frequently. The results of the regression test show that authoritative parenting styles and social-emotional stimulation have a significant positive effect on social-emotional development. The application of good authoritative parenting style and social-emotional stimulation will improve social-emotional development in both stunting and non-stunting children.